2019
DOI: 10.1139/cjfas-2018-0465
|View full text |Cite
|
Sign up to set email alerts
|

Mercury bioaccumulation in relation to changing physicochemical and ecological factors across a large and undisturbed boreal watershed

Abstract: Within a drainage basin, the position of a lake or river can greatly affect its limnological and ecological characteristics. These properties influence the cycling of mercury (Hg), a neurotoxic and bioaccumulative metal prevalent in remote northern watersheds. In this study, we examined how 43 physical, chemical, and ecological endpoints change across 58 lake and river sites within an undisturbed boreal watershed in Ontario, Canada, and assessed the influence of these endpoints on aqueous and biotic Hg concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 170 publications
0
6
0
Order By: Relevance
“…Furthermore, there is greater coverage of wetlands in the Caddy Lake watershed, which has also been linked to increased levels of mercury methylation (Hurley et al 1995; Rypel 2010; Selvendiran et al 2008). Big Whiteshell Lake appears to be more biologically productive than Caddy Lake, which is associated with lower food web mercury concentrations via dilution across greater biomass quantities (Lescord et al 2019; Rypel 2010). Black crappie in Big Whiteshell Lake have a higher observed growth rate than Caddy Lake, which is also linked to lower fish mercury levels (Borgmann & Whittle 1991; Hauger 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there is greater coverage of wetlands in the Caddy Lake watershed, which has also been linked to increased levels of mercury methylation (Hurley et al 1995; Rypel 2010; Selvendiran et al 2008). Big Whiteshell Lake appears to be more biologically productive than Caddy Lake, which is associated with lower food web mercury concentrations via dilution across greater biomass quantities (Lescord et al 2019; Rypel 2010). Black crappie in Big Whiteshell Lake have a higher observed growth rate than Caddy Lake, which is also linked to lower fish mercury levels (Borgmann & Whittle 1991; Hauger 2020).…”
Section: Discussionmentioning
confidence: 99%
“…To assess which parameters affect brook trout [THg] (standardized to 30‐cm fork length) among invaded and reference lakes, we ran a series of regression models and performed Akaike information criteria (AIC) model averaging using the R package AICmodavg (Mazerolle 2017) as per Grueber et al (2011) and Lescord et al (2019). A total of 7 models were run, one with an intercept and either lake status (i.e., invaded or reference), [DOC], FCL, trophic position, δ 13 C, or TMS as predictor variables (all normalized), as well as a null model with only an intercept term.…”
Section: Methodsmentioning
confidence: 99%
“…Complexation of Cr and Hg with nitrogen species are not commonly found in the natural environment [46][47][48][49]. Although it has been found that Hg has higher concentration in systems with more nitrates and nitrites, suggesting an indirect relationship between Hg and nitrogen cycling [50]. Pb nitrate is found to bioaccumulate in some species of plants, fish, zooplankton, crayfish, and even snails [51][52][53][54][55].…”
Section: Relationship Among the Heavy Metals And Environmental Indicatorsmentioning
confidence: 99%